Adverse reactions to amphotericin b in adults - data mining - ALINE DOS SANTOS LOUÇÃO; DÉBORA JACOMINI; JULIANA GERHARDT MORONI; ANDREIA CRISTINA CONEGERO SANCHES (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
ABSTRACT Background: Amphotericin B deoxycholate (d-AmB) is a drug widely used in fungal infections. The adverse effects of this medicine may be acute (infusion-related) or late (cumulative dose-related). Objective: This study aims to evaluate the frequency of adverse reactions to amphotericin B deoxycholate (d-AmB) in adults in a University Hospital, describe the profile of drug use in the institution and evaluate the factors related to the development of reactions with the aid of data mining. Methods: A database with the characteristics of the patients and information about the adverse reactions was created. Then, data mining was performed with the aid of WEKA software. Results: Fifteen adult patients who had used d-AmB in the selected period were identified, being 60% male. The mean age was 41.8 years old. Only 6 patients concluded their treatments with d-AmB, the others had to interrupt the treatment due to some intercurrence. Among the acute phase reactions, the most frequent were vomiting, nausea, phlebitis, hyperthermia and headache, which were related to the drug infusion. As for subacute reactions, the most frequent were urea and creatinine elevation, and hypokalemia. 30 rules were identified after data mining: d-AmB longer-term use, even with normal initial creatinine and urea, they had a greater number of acute reactions; patients with no creatinine change during d-AmB treatment had less subacute reactions; higher number of nephrotoxic drugs use, in those with increased creatinine, they presented a greater number of subacute reactions. Conclusions: The results demonstrate hat there is a relation between the time of use and the greater number of adverse reactions. This safety data help clinicians to make decisions.